Geological Recognition and Expansion Potential Analysis of the New 172-52 Drilling Area. Issue 3 (February 2021) - Zheng, Jianghua; Qiao, Shasha; Zhao, Yue; Yi, Jun; Wang, Chao
Abstract: Fine reservoir characterization is the basis of tapping the potential of high-yield exploration and evaluation wells. In this paper, the comprehensive prediction of New 172-52 reservoir in high-yield exploration and evaluation well area is carried out by using seismic data combined with drilling data, the sand body in the study area is re-depicted, and the geological understanding after drilling is integrated. It is concluded that the effective thickness of the well area on the east side of the fault in this area changes rapidly and gradually becomes thicker to the southeast, and the sand body is developed and has good connectivity, and there is potential for edge expansion above the oil-water interface. In the well area on the west side of the fault, according to the seismic reservoir attribute, the abandoned well after drilling is at the edge of the sand body, and the sand body extends to the northeast around the well point, and meets the fault block at the high part of the structure, which has the potential of expanding the edge. Through fine reservoir characterization, the boundary and scale of sand bodies are explored, and the productivity potential of high-yield exploration and evaluation wells is tapped.